1997
DOI: 10.3109/02656739709023545
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cellular cisplatin resistance by hyperthermia—a review

Abstract: Resistance to cisplatin (cDDP) is a major limitation to its clinical effectiveness. Review of literature data indicates that cDDP resistance is a multifactorial phenomenon. This provides an explanation why attempts to reverse or circumvent resistance using cDDP-analogues or combination therapy with modulators of specific resistance mechanisms have had limited success so far. It therefore provides a rationale to use hyperthermia, an agent with pleiotropic effects on cells, in trying to modulate cDDP resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 67 publications
2
72
0
2
Order By: Relevance
“…Hyperthermia also reduces the mechanisms of cellular resistance to cisplatin. [28][29][30] It has been demonstrated that heat increases cisplatin accumulation in platinum resistant cell lines. In both platinum sensitive and platinum resistant cell lines both, it sensitizes the cells for cisplatin by mechanisms like increase accumulation in the cells, increased cisplatin and DNA adduct formation and decreased removal of these adducts from the cells.…”
Section: Rationale For Hyperthermic Intraperitoneal Chemotherapy (Hipec)mentioning
confidence: 99%
“…Hyperthermia also reduces the mechanisms of cellular resistance to cisplatin. [28][29][30] It has been demonstrated that heat increases cisplatin accumulation in platinum resistant cell lines. In both platinum sensitive and platinum resistant cell lines both, it sensitizes the cells for cisplatin by mechanisms like increase accumulation in the cells, increased cisplatin and DNA adduct formation and decreased removal of these adducts from the cells.…”
Section: Rationale For Hyperthermic Intraperitoneal Chemotherapy (Hipec)mentioning
confidence: 99%
“…Eventually, DNA damage increased while DNA repair decreased. Additionally, hyperthermia was reported to have a potential ability to avoid drug resistance [86,87] . In addition, it is also expected that elevated blood flow could result in a relative increase in anticancer drug concentration within the tumor.…”
Section: Combination Therapy With Chemotherapymentioning
confidence: 99%
“…Intrinsic or acquired resistance of tumour cells to CP undermines its clinical effectiveness (Niedner et al, 2001). Mechanisms of resistance include decreased drug accumulation (Shen et al, 2000), changes in DNA repair proficiency (Fink et al, 1998;Zhen et al, 1992;Chu, 1994;Lai et al, 1995;Johnson et al, 1996), metallothionein (MT II) (Kelly et al, 1988;Kondo et al, 1995), glutathione-related enzymes (Moscow and Cowan, 1988;Godwin et al, 1992;Zaman et al, 1995), stress response proteins (Shen et al, 1995;Hettinga et al, 1997), proto-oncogenes or apoptosis-related genes, and cancer susceptibility genes (Fanidi et al, 1993;Lowe et al, 1993;DeFeudis et al, 1996;Husain et al, 1998;Moorehead and Singh, 2000). Protein kinases (PKs) like PKA and PKC have also been associated with CP-resistance (CP-r) and use of their specific inhibitors has been demonstrated to increase CP cytotoxicity in resistant tumour cells (Gosland et al, 1996).…”
mentioning
confidence: 99%